2020
DOI: 10.1021/acsomega.0c00142
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Treatment Modifies Kraft Lignin for Lignin- and Cellulose-Based Carbon Fiber Precursors

Abstract: The kraft lignin's low molecular weight and too high hydroxyl content hinder its application in bio-based carbon fibers. In this study, we were able to polymerize kraft lignin and reduce the amount of hydroxyl groups by incubating it with the white-rot fungus Obba rivulosa. Enzymatic radical oxidation reactions were hypothesized to induce condensation of lignin, which increased the amount of aromatic rings connected by carbon− carbon bonds. This modification is assumed to be beneficial when aiming for graphite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…In this case, the high levels of crystallinity in the cellulose accelerate energy dissipation. The addition of lignin, an amorphous polymer, decreases the crystallinity of regenerated fibres (Ma et al 2015;Boukir et al 2019;Mikkilä et al 2020), reducing energy dissipation, leading to an increase in loss modulus (De Nardo and Farè 2017;Shrivastava 2018). The impact of residual IL on the dynamic mechanical properties of the composite fibre in this work is considered to be negligible due to the high efficient nature of the washing process.…”
Section: Viscoelastic Properties Of Precursor Fibresmentioning
confidence: 99%
“…In this case, the high levels of crystallinity in the cellulose accelerate energy dissipation. The addition of lignin, an amorphous polymer, decreases the crystallinity of regenerated fibres (Ma et al 2015;Boukir et al 2019;Mikkilä et al 2020), reducing energy dissipation, leading to an increase in loss modulus (De Nardo and Farè 2017;Shrivastava 2018). The impact of residual IL on the dynamic mechanical properties of the composite fibre in this work is considered to be negligible due to the high efficient nature of the washing process.…”
Section: Viscoelastic Properties Of Precursor Fibresmentioning
confidence: 99%
“…It should be noted that lignin tends to leach into the coagulation bath of solution-spun lignin-containing fibers [ 124 , 136 , 225 , 227 ], which may affect the solid content and performance of the final fibers. Apart from selecting the appropriate coagulation solvent [ 124 ], lignin leaching was lessened by the incorporation of modified lignin into wet-spun cellulose-based fibers, which favored the production of biobased fibers with more lignin retained in fiber structure [ 228 ]. The modified lignin had fewer hydroxyl groups due to the enzymatic radical oxidation reactions of lignin with white-rot fungus Obba rivulosa increasing the content of aromatic rings connected by carbon/carbon (C–C) bonds.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%
“…Using the Ioncell Ò technology (Sixta et al 2015), we are able to dissolve mixtures of biopolymers in a protic ionic liquid and spin the solution into hybrid fibers. The obtained hybrid fibers are composed of two or more biopolymers forming nanoscale mixtures inside a micrometric fibrous matrix (Mikkilä et al 2020;Zahra et al 2020;Le et al 2020;Trogen et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid fibers like cellulose-lignin (Bengtsson et al 2019;Mikkilä et al 2020;Le et al 2020;Trogen et al 2021), cellulose-chitosan (Zahra et al 2020), cellulose-chitin (Ota et al 2020) or cellulose-betulin (Makarov et al 2018) have found applications in textiles (Ma et al 2015) or as precursors for biobased carbon fibers (Byrne et al 2016). The presence of a second biopolymer provides to the hybrid fiber new functional properties that can be fine-tuned by controlling the share of the biopolymer in the fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation